Tensile capacity of grouted splice sleeves. (15th March 2016) - Ling, Jen Hua; Abd. Rahman, Ahmad Baharuddin; Ibrahim, Izni Syahrizal; Abdul Hamid, Zuhairi
Highlights: Grouted splice can be used to connect steel bars at the required bar embedded length of 8 times the bar diameter. With active confinement generated in the sleeve, the tapered sleeve gives a 30% higher bond strength than the pipe sleeve. Bond strength increases with the increase of bar embedded length and the decrease of sleeve diameter. The analytical model is derived to predict the tensile capacities of the grouted splices. Abstract: This study tests grouted splices connected by two types of sleeves, namely Welded Bar Sleeve (WBS) and Tapered Head Sleeve (THS). These sleeves are made from non-proprietary pipe sections, where (a) WBS is fabricated by welding the deformed bars to the inner wall of the pipe, and (b) THS is made tapered with smaller openings at both ends. To study the behavior, the splice specimens were tested under incremental tensile load at various bar embedded lengths and sleeve diameters. The degree of confinement generated in the sleeve is found to increase with decreasing sleeve diameter. This improves the bond strength in sleeve, which subsequently increases the tensile capacity of the splice. THS gives a 30% higher tensile capacity compared with WBS. With the active confinement, the required bar embedded length of the splice can be reduced to 8 times the bar diameter. An analytical model is formulated on the basis of the confinement stress as expressed in a function of sleeve dimensions. The model is used to predict the tensile capacities of the splices at a variation range of ±10% of the experimental results. This verifies the correlations among the sleeve dimensions, the confinement stress and bond strength of the grouted splice.